Análise da ocorrência de eventos adversos associados as vacinas em crianças nos municípios da sétima regional de saúde do Estado do Paraná - Stein, Emanoeli Agnes (2022)
The investigation of after-vaccination side-effects is a strategy used to identify its causes and adopt interventions that promote safety and quality in the immunization program. The objective of this study was to identify and elaborate the profile of the main after-vaccination side effects occurred in children aged 12 years or younger reported between the years 2016 and 2020 by the 15 cities that belong to the seventh Regional Health Department of Paraná State. It is a retrospective descriptive cross-sectional study with a quantitative approach. The data were obtained through notification forms from the ministry of health system, being included only the data related to routine vaccines of the national vaccination calendar according to preconized age and excluded the ones that were duplicated or without essential information. For analysis, frequencies and associations were estimated and binary logistic regression models were used. 196 (64,68%) sideeffects associated to the vaccines and 107 (35,32%) immunization errors were identified. Regarding the side-effects, the children aged one year or younger were the most affected ones, mostly after the pentavalent vaccine, which presented 12 times more chances of incurring in side-effects. Fever and pain were the most reported side-effects and were mostly present during the first 6 hours after vaccination. Furthermore, the most frequent immunization errors were the use of expired vaccines and incorrect age group, which occurred mostly in children older than one year. All the events related to vaccination and immunization errors evolved to cure without sequels, demonstrating the benefits of vaccination. The concern of the population regarding the side-effects requires a change of attitude of the professionals in order to promote improvements in the field of immunization.